A possible origin of the large leakage current in ferroelectric Al1−xScxN films. (25th February 2021) - Kataoka, Junji; Tsai, Sung-Lin; Hoshii, Takuya; Wakabayashi, Hitoshi; Tsutsui, Kazuo; Kakushima, Kuniyuki
Abstract: Leakage current analysis on 50 nm thick ferroelectric Al0.78 Sc0.22 N films with TiN electrodes has been performed. The electron conduction followed Schottky emission with an initial Schottky barrier height ( ϕ B ) of 0.46 eV. During the initial switching, a gradual shift in the leakage current was observed, changing the ϕ B to 0.36 eV, and stayed constant for further switching cycles. From the extracted Richardson constant, the change in the ϕ B can be interpreted as the formation of a tunneling barrier due to the formation of nitrogen vacancies at the metal interface.